A Kinetic Study of Iridium(III) Chloride Catalyzed Oxidation of Diethylene Glycol by Hexacyanoferrate(III) in Aqueous Alkaline Medium - Goel, Anjali; Chauhan, Manisha (Asian Journal of Chemistry, 2016)
The iridium(III) chloride catalyzed oxidation of diethylene glycol by hexacyanoferrate(III) in aqueous alkaline medium has been studied at constant ionic strength and temperature. The reaction follows first order kinetics with respect to hydroxide ion and organic substrate at lower concentration but at higher concentrations it follows zero order kinetics. The order of reaction with respect to hexacyanoferrate(III) and iridium trichloride is unity even up to manyfold variation. A probable reaction mechanism is proposed assuming that the reaction proceeds through complex formation.